HIV/antiretroviral therapy–related lipodystrophy syndrome (HALS) is associated with higher RBP4 and lower omentin in plasma. (July 2015) - Peraire, J.; López-Dupla, M.; Alba, V.; Beltrán-Debón, R.; Martinez, E.; Domingo, P.; Asensi, V.; Leal, M.; Viladés, C.; Inza, M.-I.; Escoté, X.; Arnedo, M.; et al.
Abstract: Very little information is available on the involvement of newly characterized adipokines in human immunodeficiency virus (HIV)/antiretroviral therapy (ART)-associated lipodystrophy syndrome (HALS). Our aim was to determine whether apelin, apelin receptor, omentin, RBP4, vaspin and visfatin genetic variants and plasma levels are associated with HALS. We performed a cross-sectional multicentre study that involved 558 HIV type 1–infected patients treated with a stable highly active ART regimen, 240 of which had overt HALS and 318 who did not have HALS. Epidemiologic and clinical variables were determined. Polymorphisms in the apelin, omentin, RBP4, vaspin and visfatin genes were assessed by genotyping. Plasma apelin, apelin receptor, omentin, RBP4, vaspin and visfatin levels were determined by enzyme-linked immunosorbent assay in 163 patients (81 with HALS and 82 without HALS) from whom stored plasma samples were available. Student's t test, one-way ANOVA, chi-square test, Pearson and Spearman correlations and linear regression analysis were used for statistical analyses. There were no associations between the different polymorphisms assessed and the HALS phenotype. Circulating RBP4 was significantly higher (p < 0.001) and plasma omentin was significantly lower (p 0.001) in patients with HALS compared to those without HALS; differences in plasma levels of the remaining adipokines were nonsignificant between groups. Circulating RBP4 concentration was predicted independently by the presence of HALS. Apelin and apelin receptor levels were independently predicted by body mass index. Visfatin concentration was predicted independently by the presence of acquired immunodeficiency syndrome. HALS is associated with higher RBP4 and lower omentin in plasma. These two adipokines, particularly RBP4, may be a link between HIV/ART and fat redistribution syndromes.